Assesment of construction planning : maintenance of piping system at Bukit Sekilau Kuantan case study - Nur Syazana, Jusoh (2018)
Construction sector is a very important and productive sector in the Malaysian economy. A project is considered successful if it can be completed at an estimated cost, within a scheduled period and in accordance with specified quality specifications. However, there are also contractors failing to complete the project within a scheduled period. There is a possibility that this situation can be caused by the time set is less precise. The main objective of this study is construction planning to maintain the piping system in Bukit Sekilau, Kuantan. Existing schedule planning has been analyzed to identify factors that cause delays in the project. After identifying the factors affecting the delay of the project, reschedules planning were made taking into account the number of days of rain, the number of public holidays and the number of days required to obtain approval from the parties concerned. Therefore, optimum planning can be achieved and the project can be completed on time, cost, quality and operations can be implemented in line with the plan. After obtaining optimum working days in construction planning, certain recommendations can be made in order to improve construction planning and can be the guideline for future construction planning.